REPRODUCTIVE HEALTH OF WOMEN AFTER SURGICAL TREATMENT OF ACUTE PURULENT INFLAMMATORY DISEASES OF UTERINE APPENDAGES - Константин Александрович Тониян; Дмитрий Геннадьевич Арютин; Александра Андреевна Белоусова (The Publishing House Medicine and Enlightenment, 2018)
The aim of the study was to optimize management tactics and improve outcomes in patients with acute purulent diseases of the uterus after surgical treatment. Materials and methods.In the period from 2015 to 2017 in the departments of gynecology in clinical bases of the Department of obstetrics and gynecology with a course of perinatology of the medical faculty of the Medical Institute of the Russian University of Friendship of Peoples was conducted a comprehensive examination and treatment of 150 patients with acute purulent diseases of the uterus. Results. All patients were operated on urgently laparoscopic access in the volume of unilateral adnexectomy. In the course of the study the majority of the examined patients was observed violation of the microbiome of the vagina. Comparative analysis of the microflora separated from the abdominal cavity and the material from the cervical canal revealed a low level of coincidence of the results of cultural and molecular genetic studies. However the frequency of detection of sexually transmitted infections did not depend on the location of the material intake. The treatment tactics of management of patients offered by us including a number of modern technologies and methods of treatment, allowed to restore reproductive function almost at a quarter of the examined women. Conclusion. Rational tactics of management of patients with acute purulent diseases of uterus appendages includes: pathogenetic matched preoperative preparation, an adequate volume of surgical interventions with the elimination of the purulent center, using the latest anesthetic techniques and modern complex of postoperative rehabilitation with a personalized selection of antimicrobial and antibiotic therapy.